Iatrogenic common bile duct injuries: Increasing complexity in the laparoscopic era: A prospective cohort study. (September 2016) - Hogan, N.M.; Dorcaratto, D.; Hogan, A.M.; Nasirawan, F.; McEntee, P.; Maguire, D.; Geoghegan, J.; Traynor, O.; Winter, D.C.; Hoti, E.
Abstract: Purpose: Iatrogenic bile duct injury (BDI) is the most significant associated complication to laparoscopic cholecystectomy (LC). Little is known about the evolution of the pattern of BDI in the era of laparoscopy. The aim of the study is to assess the pattern of post-LC BDIs managed in a tertiary referral centre. Methods: Post-LC BDI referred over two decades were studied. Demographic data, type of BDI (classified using the Strasberg System), clinical symptoms, diagnostic investigations, timing of referral, post-referral management and morbidity were analysed. The pattern of injury, associated vascular injuries rate and their management were compared over two time periods (1992–2004, 2005-2014). Results: 78 BDIs were referred. During the second time period Strasberg A injuries decreased from 14% to 0 and Strasberg E1increased from 4% to 23%, the rate of associated vascular injury was six time higher (3.6% versus 22.7%), more patients had an attempted repair at the index hospital (16% versus 35%) sand fewer patients could be managed without surgical intervention at the referral hospital (28% versus 4%). Conclusion: Complexity of referred BDIs and rate of associated vascular injuries have increased over time. These findings led to more patients managed requiring surgical intervention at the referral hospital. Highlights: Bile duct injuries (BDI) are frequent and often invalidating complications of laparoscopic cholecystectomies and their complexity increased overtime. The rate of vascular injuries associated to BDI increased six times in the second period of the study. Surgeons must be aware of the increased complexity of bile duct injuries associated with laparoscopic cholecystectomy.